2019
DOI: 10.1111/2041-210x.13251
|View full text |Cite
|
Sign up to set email alerts
|

Using radiotelemetry to study behavioural thermoregulation in insects under field conditions

Abstract: Thermoregulation is a central aspect of animal physiology. Mobile ectotherms have the potential to influence their temperature through their location and orientation. Behavioural thermoregulation has been extensively studied in insects, particularly in the migratory locust Locusta migratoria. However, most field studies are confined to daytime observations typically using invasive thermocouples with obvious potential to disrupt natural behaviour. We demonstrate that miniature radiotransmitters represent an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Ectotherms rely on behavioural modifications to seek heat sources in the environment (e.g., sun-basking). Oedaleus senegalensis was shown to exhibit sunbathing behaviour, i.e., it tended to head east in the mornings to warm up [31], and Rskov et al collected evidence of behavioural themoregulation in L. migratoria at dusk and dawn [39]. Moreover, this study revealed that the average T b of the nymphs depended more strongly on environmental conditions than did that of the adults.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Ectotherms rely on behavioural modifications to seek heat sources in the environment (e.g., sun-basking). Oedaleus senegalensis was shown to exhibit sunbathing behaviour, i.e., it tended to head east in the mornings to warm up [31], and Rskov et al collected evidence of behavioural themoregulation in L. migratoria at dusk and dawn [39]. Moreover, this study revealed that the average T b of the nymphs depended more strongly on environmental conditions than did that of the adults.…”
Section: Discussionmentioning
confidence: 53%
“…We fitted the daytime temperatures (centred at 12:00) as linear, quadratic, and cubic terms in the linear part of the model and fitted a random effect hour of recording [38]. Binary predictors were centred to zero, such that slopes could be used to estimate the differences among the groups, though the main effects remained interpretable in the presence of interactions [39]. Firstly, mixed model statistical analyses were performed to determine the influence of time, sex, and colour morph on the measured and calculated parameters.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Marking methods should also preserve locomotor performance, because it can favor survival through improved ability to forage (Budick and O'Malley, 2000;Higham, 2007), allowing refuge use (Martín and López, 2000), or fleeing from predators (Arendt, 2009;McGee et al, 2009;Oufiero et al, 2011). Indeed, most animals rely on their escape ability to elude predators (Lima and Dill, 1990;Cooper and Blumstein, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotelemetry is a moderately invasive tool for animal tracking (Cagnacci et al, 2010). The progressive reduction in size of the devices that animals must carry for radiotelemetry is increasing its usefulness in small animals (Ørskov et al, 2019), but radiotelemetry (and also DNA-tagging) is an expensive method that cannot always be implemented. Consequently, estimates of survival frequently require a capture–recapture technique (Besbeas et al, 2002; Cordero-Rivera and Stoks, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Like plants, small ectotherms such as insects are acutely exposed to climatic variables and do not typically use metabolism to maintain their temperature. However, unlike plants, they have the potential to use behaviour to modify their exposure to the environment by moving (Kearney et al., 2009; May, 1979; Ørskov et al., 2019). Most studies of local adaptation examine changes across large‐scale environmental clines.…”
Section: Introductionmentioning
confidence: 99%